P4S and CCAFS WA inform investment design for AfDB's Sahel and Congo Basin Investments ($1.3 billion) under African Development Bank's Africa CSA Programme - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
In 2017, P4S, with CCAFS-WA, informed the CSA Program of the African Development Bank, intended to create a portfolio of $2 billion investment. We provided inputs into the Concept Note (2017), that increased the breadth. The program was launched at the GACSA in 2017. In 2018, P4S participated in the development of Central Africa and Sahel investments (1.3 billion) under the CSA program. These investments use AfDB pipeline investments to leverage GCF/GEF co-funding and will begin in 2019.